Informasi Objek Wisata di Bungus Teluk Kabung Berbasis Web - Neril, Ninda Kurnia; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this study is to describe how to find information about the existing tourism objects in Bungus Teluk Kabung. Using PHP Programing (hyperlink prepreccssor) web based aplication. This application was used as a tool to find information about wisata objectsÂ  field. Descriptive method with data collection technique through observation , interview, and library in study to library. From the observation and interview was data as a material to design a website that made as a medium of information and promotion in Bungus it, can be summarized as follows: first, technology has become a leading thing in all fields. second, this website is dynamic by using the aplication framework codeigmite (Ci), which is one of the software that is designed specifically in designing the website. Keyword: information about the existing tourist